THE NATURE OF THE LEGALITY OF CRIMES OF NECESSITY - Basha Al Bajali, Abul Firdaus Bayinat (International Journal For Research In Social Science And Humanities, 2021)
The scholars - may God Almighty have mercy on them - have limited the necessities without which there is no life in five faculties in which all the molecules necessary for life fall. A person’s life is cut off, and if there is a difference between the nations regarding the preservation of these necessities, it is in the manner of preserving them, not in their origin. The research has been called the nature of legitimacy for crimes of necessity; Because the meaning of necessity is a comprehensive meaning that touches on many matters, and a person must be characterized by reconciliation with himself and with others, and the noble Islamic Sharia has considered that any aggression that occurs against these universals or one of them is considered a crime in the eyes of Sharia that deserves the punishment specified by the Sharia. Islam did not leave the matter in vain, as the Almighty said: (ﮚ ﮛ ﮜ ﮝ ﮞ) but rather set the limits And enact the way to know what is beneficial that must be sought and commanded, and what is harmful must be avoided and abstained from. And all of this came through the provisions that God enacted for his servants. As these commands and prohibitions are the sections of the ruling with which the Islamic street addressed the taxpayers. In this research, I dealt with some of the rulings on a number of issues in advance by defining them and explaining their divisions as follows: Definition of governance and its divisions, intention and permission, legal nature of necessity, comparison between Sharia and law in the nature of necessity, I have interpreted the verses, explained the hadiths, criticism and deduction, and listed the opinions of scholars and tried to explain the most correct one. Using the analytical method, then it showed the teachings to which the verses guide us, which must be applied in dealing with people through the applied approach.